2023
DOI: 10.3389/fcimb.2023.1191126
|View full text |Cite|
|
Sign up to set email alerts
|

Alterations of gut microbiome following gastrointestinal surgical procedures and their potential complications

Abstract: Intestinal microorganisms play a crucial role in shaping the host immunity and maintaining homeostasis. Nevertheless, alterations in gut bacterial composition may occur and these alterations have been linked with the pathogenesis of several diseases. In surgical practice, studies revealed that the microbiome of patients undergoing surgery changes and several post-operative complications seem to be associated with the gut microbiota composition. In this review, we aim to provide an overview of gut microbiota (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 126 publications
0
0
0
Order By: Relevance
“…Surgery can alter the composition of the gut microbiome in the gastrointestinal tract. 32 Therefore, surgery might also impact the gut microbiome composition in the kidney, and some of these changes could be reflected in the blood after surgery.…”
Section: Cutibacterium Acnes-derived Evs Promote Tumor Growth In Vivomentioning
confidence: 99%
“…Surgery can alter the composition of the gut microbiome in the gastrointestinal tract. 32 Therefore, surgery might also impact the gut microbiome composition in the kidney, and some of these changes could be reflected in the blood after surgery.…”
Section: Cutibacterium Acnes-derived Evs Promote Tumor Growth In Vivomentioning
confidence: 99%
“…Clinical studies have shown that factors such as traction during surgery and general anesthesia can result in poor postoperative gastrointestinal function recovery in patients, which not only affects the patients' recovery outcomes but also their quality of life. Additionally, due to the large surgical incision, patients need to use pain pumps, further exacerbating gastrointestinal dysfunction[ 9 ]. For example, common clinical manifestations include cessation of flatulence and bloating, which require surgical intervention for treatment.…”
Section: Introductionmentioning
confidence: 99%